In-vitro investigation of magnetron-sputtered coatings based on silicon-substituted hydroxyapatite; Journal of Surface Investigation. X-ray, Synchrotron and Neutron Techniques; Vol. 5, iss. 6 - Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich; Pichugin V. F. Vladimir Fyodorovich; Chernousova S. S.; Epple M. (2011, 2011)
Title screen